Voices from the developing nations of Asia and the Pacific: deliberations on the problematisations by the editors about the Global South. Issue 2 (15th March 2022) - Saito, Eisuke
ABSTRACT: Some of the problems addressed by the editors of the Asia-Pacific Journal of Teacher Education (APJTE) refer to the issues concerning the Global South. This commentary elaborates upon the problematisations by the editors with reference to the ethical challenges arising in contexts of political turmoil; issues related to the power, or lack of it, of transnational organisations; and challenges faced by researchers from developing countries to publish their works in international journals. The commentary argues that the APJTE can, and should, contribute to solving the aforesaid issues and function as a platform for exchange of views, knowledge, and ideas among scholars from the developing nations of Asia and the Pacific and their counterparts from developed countries. In this context, substantial attention should be paid to the problems in those areas in the form of special issues, in addition to publication of articles in regular issues; an establishment of a new category for shorter pieces or commentaries should be considered; and online sessions should be organised for researchers in developing countries of Asia and the Pacific about how to publish with the APJTE.